The Problems of Moral Education in Theory and Practice of “Active School” - Valatkienė, Stasė (Acta Paedagogica Vilnensia, 2000)
The article analyses the different outlooks of “active school” to moral education in the beginning of the 20th century in the West Europe and USA. Based on comparative analysis, the article reviews attitudes of various authors (J. Dewey, F. Foerster, M. Montessori and others) towards the child and towards the main principles, the content, forms and methods of moral education. The author presents international conferences and international researches of moral education problems. The ideas of “new education” reflected in the searches of educators in Lithuania. The author draws the conclusion that all searches were more partial, the universal theory of moral education wasn’t founded.